Respuesta :

Answer:

The values in the table, taking into account the quadratic equation, are:

  • x     -3     -2     -1     0     1     2     3     4
  • y     16      9     4     1     0     1     4     9

Step-by-step explanation:

To obtain the values of the table, you must use the quadratic equation given:

  • y = x^2 - 2x + 1

Now, you must replace the x with the one that is above the value you want to find, in the first case, we're gonna replace the value x with -3:

  • y = x^2 - 2x + 1
  • y = (-3)^2 - 2*(-3) + 1
  • y = 9 + 6 + 1
  • y = 16

When x is -1

  • y = x^2 - 2x + 1
  • y = (-1)^2 - 2*(-1) + 1
  • y = 1 + 2 + 1
  • y = 4

When x is 1

  • y = x^2 - 2x + 1
  • y = (1)^2 - 2*(1) + 1
  • y = 1 - 2 + 1
  • y = 0

When x is 3:

  • y = x^2 - 2x + 1
  • y = (3)^2 - 2*(3) + 1
  • y = 9 - 6 + 1
  • y = 4

At last, the graph must be as the attached picture I give you, but remember in y-axis you must use 1 cm as unit and in the x-axis you must use 2 cm as unit, in this form, the graph will not be so elongated as the picture I attach, It would be wider.

Ver imagen yersanabria
ACCESS MORE